Effects of two immunosuppressive treatment protocols for IgA nephropathy - Rauen, Thomas; Sommerer, Claudia; Zeier, Martin; Benck, Urs Tobias (Journal of the American Society of Nephrology, 2018)
The role of immunosuppression in IgA nephropathy (IgAN) is controversial. In the Supportive Versus Immunosuppressive Therapy for the Treatment of Progressive IgA Nephropathy (STOP-IgAN) Trial, 162 patients with IgAN and proteinuria >0.75 g/d after 6 months of optimized supportive care were randomized into two groups: continued supportive care or additional immunosuppression (GFR≥60 ml/min per 1.73 m2: 6-month corticosteroid monotherapy; GFR=30-59 ml/min per 1.73 m2: cyclophosphamide for 3 months followed by azathioprine plus oral prednisolone). Coprimary end points were full clinical remission and GFR loss ≥15 ml/min per 1.73 m2 during the 3-year trial phase. In this secondary intention to treat analysis, we separately analyzed data from each immunosuppression subgroup and the corresponding patients on supportive care. Full clinical remission occurred in 11 (20%) patients receiving corticosteroid monotherapy and three (6%) patients on supportive care (odds ratio, 5.31; 95% confidence interval, 1.07 to 26.36; P=0.02), but the rate did not differ between patients receiving immunosuppressive combination and controls on supportive care (11% versus 4%, respectively; P=0.30). The end point of GFR loss ≥15 ml/min per 1.73 m2 did not differ between groups. Only corticosteroid monotherapy transiently reduced proteinuria at 12 months. Severe infections, impaired glucose tolerance, and/or weight gain in the first year were more frequent with either immunosuppressive regimen than with supportive care. In conclusion, only corticosteroid monotherapy induced disease remission in a minority of patients who had IgAN with relatively well preserved GFR and persistent proteinuria. Neither immunosuppressive regimen prevented GFR loss, and both associated with substantial adverse events.
Published online before print October 17, 2017
Gesehen am 16.04.2018